A methodology for preparing a list of recommended regulated non‐quarantine pests (RNQPs). (2nd November 2017) - Picard, C.; Ward, M.; Benko‐Beloglavec, A.; Matthews‐Berry, S.; Karadjova, O.; Pietsch, M.; Van Der Gaag, D. J.
Abstract : The concept of 'regulated non‐quarantine pest' (RNQP) was introduced in the revised text of the FAO International Plant Protection Convention (IPPC) approved in 1997. Measures against quarantine pests (exclusion, eradication, containment) aim to prevent unacceptable economic, environmental and social impacts resulting from the introduction and/or spread of these pests. On the contrary, the concept of RNQPs is intended to prevent an unacceptable economic impact on the intended use of plants for planting by pests that are already present in the area. RNQPs have been introduced in the new EU plant health regulation, in line with available international standards. This regulation entered into force in December 2016 and will be implemented in the following 3 years. In this context, EPPO agreed to undertake a 2‐year project on RNQPs: the EU Quality Pest Project. The objective of this project was to develop a methodology and then to apply this methodology to a list of about 1400 pest–host combinations to identify which should be recommended as RNQPs. This methodology is presented in this paper, as well as the main issues discussed during its development.